Institutional Strengthening of the Pancer Beach Tourism Community Group in Growing Community Participation in the Puger Jember Region - Aroziki, M. Maulada Khoirul Wava; Indrianti, Deditiani Tri; Sintiawati, Nani (Program Studi Pendidikan Luar Sekolah FKIP Universitas Jember, 2024)
This study aims to determine the form of institutional strengthening carried out by the Pancer Puger Beach Tourism Community Group (Pokmas) in an effort to resolve the problems of the characteristics of coastal communities and forms of coastal community participation as a result of institutional strengthening. The research method used by researchers is a qualitative approach with data collection techniques through interviews, observation, and documentation. The results of the research show that institutional strengthening is an effort to build the right organization, partnerships, human resources, and processes to carry out certain plans or agendas. Community Participation is the ability possessed by community members to be involved in development activities with a sense of awareness and accountability for the potentials that can be utilized in their environment. Institutional strengthening found in this study includes institutional capacity building, human resource capacity building, service capacity building, and partnership network expansion. Meanwhile, the form of coastal community participation as a result of institutional strengthening includes economic participation, environmental participation, and socio-cultural participation